Kajian Infrastruktur Ramah Lingkungan Di Perkotaan - ERVIANTO, Wulfram I. (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2019)
The city is an important part of the population as a space to work and socialize with fellow residents who occupy it. Not surprisingly, most of the population moves towards the city to get a more established livelihood. Data shows that the majority of the population living in the villages began to move to the city for various reasons, as indicated by the high rate of urbanization from year to year. One day the village will lose its role as a food barn for residents of the region. On the other hand, infrastructure needs in urban areas tend to increase which results in a decline in natural resources, especially those that are not renewable.To maintain a balance between the capabilities of nature providing various types of natural resources and infrastructure needs that continue to increase from year to year. The right approach is needed by implementing environmentally friendly development. This study discusses environmentally friendly approaches that are implemented in several infrastructures, namely (1) Eco-friendly sea port consisting of 23 important factors, (2) Environmentally friendly airport consisting of eight aspects, (3) environmentally friendly train station that covers three aspects, (a) in the train station environment, (b) along the railroad, through a tree planting greening program that absorbs CO_2 emissions, (c) Appropriate use of water quality and amount, for toilet purposes on trains using used water or rainwater harvested during rain.